Information Technology on Accounting Information System - Puspitawati, Lilis; Herliani, H R; Agustin, N; Fauzan, R R (Universitas Komputer Indonesia, 2024)
Information technology's role in various aspects of business activities nowadays focuses on using information systems to process financial transactions. With the help of information technology, business people can meet their information needs quickly, on time, relevant, and accurately. This study aims at determining the dimensions used in measuring the quality of information technology and the effectiveness of accounting information systems. Besides, it is also to determine the positive or negative impacts caused by changes in Information Technology on the efficacy of Accounting Information Systems. This research used an experimental method. The data collection is done by conducting a literature study and interviews with several informants who use accounting information systems to MSME business players in Bandung City. The results of this study indicate that the determination of the development of Information Technology has proven to have a positive effect on the effectiveness of the Accounting Information System. User satisfaction and system use are the dimensions most widely used to measure the effectiveness of information systems, and hardware, software, brainware, and communication networks are the dimensions most widely used by researchers to measure the quality of information technology